The Influence of Motivation as an Intervening Variable on the Relationship Between Work Climate and Organizational Culture with Innovative Work Behavior in Society 5.0 Era (Study on Employees at JMC Electronics Kaohsiung) - Feldiannisa, Toyunda Nurva (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of motivation as an intervening variable on the relationship between work climate and organizational culture with innovative work behavior. This research consists of two independent variables, one dependent variable and one intervening variable. The independent variables in this study are work climate and organizational culture. The dependent variable in this study is innovative work behavior. The intervening variable in this study is motivation. The population in this study were all JMC Electronics employees in Kaohsiung City. The sample used simple random sampling, amounting to 112 respondents. Data collection techniques were carried out using a questionnaire. Analysis of research data used SEM (Structural Equation Modeling) analysis which was operated through the AMOS 24.0 program. The results of this study indicate that work climate and organizational culture have no significant effect on innovative work behavior. However, motivation has a significant positive effect on innovative work behavior and work climate and organizational culture have a significant positive effect on motivation.